Factors associated with condom use in women from an urban area in southern Brazil - Mariângela Freitas da Silveira; Iná Silva dos Santos; Jorge Umberto Béria; Bernardo Lessa Horta; Elaine Tomasi; Cesar Gomes Victora
This study investigated the prevalence of factors associated with condom use during last sexual intercourse in 15-49-year-old women in a probabilistic sample from the urban area of Pelotas, southern Brazil. A questionnaire administered by an interviewer, investigating socioeconomic characteristics and habits, and another (self-administered) questionnaire on sexual behavior-related variables were used. Poisson regression, following a hierarchical model, was used for data analysis. 1,543 women were included, and losses and refusals amounted to 3.5%. Prevalence of condom use in last sexual intercourse was 28.0%. Condom use was positively associated with younger age, greater schooling, non-white color, single marital status, and greater number of sex partners in the previous three months. This suggests that the group most vulnerable to STDs/AIDS due to lack of condom use is white, adult women, in stable unions, with fewer sexual partners.